First comparative evaluation of a new leukapheresis technology in non‐cytokine‐stimulated donors. (24th October 2013) - Steininger, P. A.; Strasser, E. F.; Weiss, D.; Achenbach, S.; Zimmermann, R.; Eckstein, R.
<x xml:space="preserve">Abstract</x> Background and Objectives Leukapheresis is an important source for mononuclear cells (MNCs) used in adoptive immunotherapies. Differences in the apheresis technology concerning physical conditions during cell separation and the optical detection system can affect the product's cellular content. Materials and Methods In a paired analysis, twenty healthy non‐cytokine‐stimulated donors underwent MNC collection at the Spectra Optia (Terumo BCT, Lakewood, CO, USA) and the COM.TEC (Fresenius Kabi, Bad Homburg, Germany) device. In twelve donors, apheresis was additionally performed with the Amicus (Fenwal Inc., Lake Zurich, IL, USA). Donor response to leukapheresis and product composition was compared. Results Mean yields of CD14+ (CD3+) cells were 1·64 ± 0·70x109 (2·36 ± 0·96 × 109) in the Spectra Optia, 1·45 ± 0·50 × 109 (3·03 ± 1·04 × 109) in the COM.TEC and 1·20 ± 0·37 × 109 (2·80 ± 1·00 × 109) in the Amicus products, respectively. The Spectra Optia collected significantly more CD14+ monocytes than the Amicus and significantly less CD3+ T cells than the COM.TEC (P = 0·002 and P = 0·021). Apheresis products of the Spectra Optia showed the significantly lowest red blood cell yields while the Amicus generated products with the significantly lowest platelet contents. Conclusions Leukaphereses with the three devices resulted in almost equal total MNC yields. MNC products of the Spectra Optia and the Amicus could be used in preference for the monocyte enrichment by the Elutra system and the leukapheresis procedures could be also favourably applied in patients with low platelet counts. The COM.TEC is more efficient in monocyte and T‐cell collection with the disadvantage of high residual non‐target cell content in the products.